الأسباب الداخلية للتعديل في السياسة النقدية في سورية - الخليل, فادي; أبا زيد, ثناء; زريق, نسرين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
في ظل التطورات الاقتصادية العالمية الحالية و ضرورة مواكبة سورية لها (الأمر الذي أصبح ضرورة وليس خياراً) نشأت الضرورة إلى القيام بالتعديل في السياسة النقدية في سورية من قبل المحللين الاقتصاديين. وقد تعرضنا في بحثنا إلى دراسة خصائص النظام النقدي السوري من حيث تجميد أحكامه والغياب المطلق فيه للسلطة النقدية و تهميش دور مصرف سورية المركزي في رسم وتنفيذ السياسة النقدية. وقد توصلنا في النهاية إلى بعض النتائج والتوصيات التي يمكن أن تساهم في تفعيل التعديلات في السياسة النقدية بما يحقق النتيجة المرجوة منها. Given the present international economic developments and the necessity for Syria to go along with them (which is not an option any more), the need has arisen for economic analysts to change the Syrian monetary policy. In this paper, we study the properties of the Syrian monetary system through the freezing of its rules, the initial absence of monetary power, and the marginal role of the Central Bank of Syria in implementing the monetary policy. Finally, we have shown the results of this study, presenting a number of suggestions which may contribute to achieving the desired results.